ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN GAS CNG UNTUK KENDARAAN BBG DI KOTA PALEMBANG - Reza Helfani; Hasril Atieq Pohan (Yonetim Jurnal, 2021)
This study aims to determine the magnitude of the influence of the marketing mix on the decision to purchase CNG gas for CNG vehicles in Palembang City, and to determine which variables are dominant in influencing it. The results of this study indicate that the overall marketing mix variable influences purchasing decisions, with the product variable value of 17.9%, the price variable of 19.7%, the distribution channel variable of 34.4% and the promotion variable of 32.5%. Of the four marketing mix variables as a whole affect purchasing decisions with a correlation value of 68.5%. Overall, the marketing mix variables affect purchasing decisions, but the distribution channel variables have the greatest influence on consumers in making purchasing decisions. This shows that consumers' desire to use CNG gas is strongly influenced by the location of the SPBG. The more SPBG locations, the higher interest in vehicles using CNG will be. Keywords: Marketing Mix, CGN Gas Purchase Decision